PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BIDANG PENDIDIKAN KANTOR SEKRETARIAT WILAYAH KECAMATAN CERMEE KABUPATEN BONDOWOSO - Farida Hanum; Elisa Nurul Fadilah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2019)
The formulation of the problem in this study is whether there is an influence of organizational culture on the performance of employees of the Education Sector Office of the Secretariat of the District of Cermee, Bondowoso Regency. The research method in this thesis is including quantitative research using quantitative research, with a survey approach that is research that takes samples from the population and uses a questionnaire as a primary data collection tool. In this study, as many as 18 people were sampled using a total sampling technique or saturated samples. The data analysis method uses validity test and reliability test while to test the hypothesis in this study it can use test, multiple linear regression analysis, partial test (t test) assisted by SPSS 22.0 for windows. With a significance level of 0.05 and determination of acceptance and rejection criteria. The results of the analysis conducted by researchers note that with a significance level of 0,000 so the value of tcount is 7.985> table 2.119. Based on the significance value, it can be concluded that the significance value of 0,000 is below 0.05, which means that Ho is rejected and Ha is accepted, this shows that there is an influence of organizational culture on the performance of Education Sector Officers in the Regional Secretariat Office of Cermee Subdistrict, Bondowoso Regency